LEAF NUTRIENT STATUS IN THE LOWLAND DIPTEROCARP FOREST - SOEDARSONO Riswan (Research Center for Biology, 1988)
Study on leaf nutrient status in the primary lowland dipterocarp forest has been carried out at Mulawarman University research forest, Lempake, Samarinda. Six elements i.e. N, P, K, Na, Ca and Mg were analyzed. Results show that the dominant species and family seemed to be controlling and maintenance the main mineral nutrients in this forest ecosystem. There were a variation of mineral nutrients between species and also a fluctuation of mineral nutrients in the different period.